Impact of Ratification of Government Regulations Substituting Law Number 2 of 2017 Becomes Act on Society in Running Activities of Islamic Community Organizations in Indonesia - Ferry Irawan Febriansyah (Al-Hayat: Journal of Islamic Education, 2018)
The adoption of government regulations instead of law number 2 of 2017 instead of law number 17 of 2013 concerning community organizations certainly creates a lot of polemic in society. The controversy gave rise to the pros and cons of the law. The community feels freedom in organizing is castrated, while on the other hand, some people agree with the new law and this has an impact on society. The result in society is an unusual social symptom to study, considering that there are so many forms of community organizations in the Unitary State of the Republic of Indonesia. The number of kinds of community organizations, the government feels that a new regulation is needed, namely perppu number 2 of 2017 instead of law number 17 of 2013 concerning community organizations that have passed into law. With the enactment of Perppu number 2 of 2017 into law, there have been many turmoils in the community in responding to this matter, starting from those who agree and those who do not conform to the promulgation of the Perppu, but the impact in the community is not significant because the organizations legally dissolved they are illegal, they still run religious activities as they should by not violating applicable laws.Disahkannya peraturan pemerintah pengganti undang-undang nomor 2 tahun 2017 pengganti undang-undang nomor 17 tahun 2013 tentang organisasi kemasyarakatan tentunya menimbulkan banyak polemik di dalam masyarakat. Polemik tersebut memunculkan pro dan kontra tentang undang-undang tersebut. Masyarakat merasa kebebasan dalam berorganisasi terkebiri, sedangkan di sisi lain sebagian masyrakat setuju dengan aturan hukum baru tersebut dan hal inilah yang menimbulkan dampak di dalam masyrakat. Dampak di dalam masyarakat merupakan gejala sosial yang menarik untuk diteliti, mengingat begitu banyak bentuk organisasi kemasyarakatan yang ada di Negara Kesatuan Republik Indonesia. Banyaknya bentuk organisasi kemasyarakatan, pemerintah merasa perlu dibentuk regulasi baru yaitu perppu nomor 2 tahun 2017 pengganti undang-undang nomor 17 tahun 2013 tentang organisasi kemasyrakatan yang telah disahkan menjadi undang-undang. Dengan disahkannya perppu nomor 2 tahun 2017 menjadi undang-undang, banyak gejolak di dalam masyrakat dalam menyikapi hal tersebut, mulai dari yang setuju dan yang tidak setuju diundangkannya perppu tersebut, akan tetapi dampak di masyarakat tidak terlalu signifikan dikarenakan ormas yang mendapat sanksi pembubaran secara hukum mereka illegal, secara kegiatan keagamaan tetap mereka jalankan sebagaimana mestinya dengan tidak melanggar undang-undang yang berlaku.